2021
DOI: 10.4132/jptm.2021.07.29
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of interobserver variability in pathologic diagnosis of papillary breast lesions on core needle biopsy with WHO classification

Abstract: Background: Papillary breast lesions (PBLs) comprise diverse entities from benign and atypical lesions to malignant tumors. Although PBLs are characterized by a papillary growth pattern, it is challenging to achieve high diagnostic accuracy and reproducibility. Thus, we investigated the diagnostic reproducibility of PBLs in core needle biopsy (CNB) specimens with World Health Organization (WHO) classification. Methods: Diagnostic reproducibility was assessed using interobserver variability (kappa value, κ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, differentiating EPC from other papillary breast lesions is difficult when using preoperative core needle biopsies and having to rely on surgical excision to obtain accurate pathological diagnoses ( 10 ). Moreover, it has been suggested that pathologists are often confused regarding the displaced fragments of tumor tissue outside the fibrous capsule and true invasion ( 29 ). Additionally, a newly proposed variant of invasive lobular carcinoma may sometimes morphologically mimic EPC growth patterns ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiating EPC from other papillary breast lesions is difficult when using preoperative core needle biopsies and having to rely on surgical excision to obtain accurate pathological diagnoses ( 10 ). Moreover, it has been suggested that pathologists are often confused regarding the displaced fragments of tumor tissue outside the fibrous capsule and true invasion ( 29 ). Additionally, a newly proposed variant of invasive lobular carcinoma may sometimes morphologically mimic EPC growth patterns ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Papillary neoplasms of the breast comprise a broad range of proliferative diseases, including non-cancerous and abnormal growths, as well as malignant lesions. They constitute less than 3% of all breast lesions ( 1 , 2 ). According to the latest WHO classification of breast tumors (5th edition), papillary neoplasms of the breast include benign and malignant lesions ( Table 1 ) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%